2018
DOI: 10.1002/fsn3.736
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of volatile flavor compounds in nkui (a Cameroonian food) by solid phase extraction and 2D gas chromatography time of flight mass spectrometry (SPMEGC×GCTOFMS)

Abstract: The objective of this study was to investigate the volatile flavor compounds of nkui, a Cameroonian food, using solid phase microextraction (SPME) and a two‐dimensional gas chromatography time of flight mass spectrometry GC×GC‐TOF‐MS system. Using SPME, volatile compounds were extracted from nkui and analyzed by GC×GC‐TOF‐MS. The data retrieved revealed the presence of flavor volatiles including acids (20%), alcohols (4%), aldehydes (10%), aromatic compounds (4%), esters (7%), furans (4%), ketones (11%), terpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
(26 reference statements)
0
7
1
Order By: Relevance
“…Using solid phase microextraction and a two-dimensional gas chromatography time of flight mass spectrometry (GC × GC-TOF-MS) system, flavor volatiles of Afrostyrax lepidophyllus was shown to contain mainly terpenes and terpernoids [15]. This difference with our results could be due to conservation methods and methods of extraction.…”
Section: Gc-ms Profilecontrasting
confidence: 96%
“…Using solid phase microextraction and a two-dimensional gas chromatography time of flight mass spectrometry (GC × GC-TOF-MS) system, flavor volatiles of Afrostyrax lepidophyllus was shown to contain mainly terpenes and terpernoids [15]. This difference with our results could be due to conservation methods and methods of extraction.…”
Section: Gc-ms Profilecontrasting
confidence: 96%
“…The phenomenon occurred may be related to the action of enzymes, which could reduce the aldehydes produced by the catabolism of fatty acids and amino acids to the corresponding alcohols ( Chen et al., 2009 ). Among alcohol compounds ( Table 3 ), 3,7-dimethyl-1,6-octadien-3-ol is commonly known as linalool and has a floral, citrus-like aroma ( Adebo et al., 2018 ), of which the content was higher in CS. Terpinen-4-ol has a woody, earthy, and musty aroma ( Adebo et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among alcohol compounds ( Table 3 ), 3,7-dimethyl-1,6-octadien-3-ol is commonly known as linalool and has a floral, citrus-like aroma ( Adebo et al., 2018 ), of which the content was higher in CS. Terpinen-4-ol has a woody, earthy, and musty aroma ( Adebo et al., 2018 ). It has been demonstrated that terpenoids including 3,7-dimethyl-1,6-octadien-3-ol, terpinen-4-ol, isopinocarveol, α-acorenol, and 9-octadecen-1-ol were the major sources of natural flavor additives in foods and fragrances ( Singh and Sharma, 2015 ), with those content was slower despite in the CB or CS.…”
Section: Resultsmentioning
confidence: 99%
“…Aldehydes are not only flavor components, but also known as vital reactants associated with heterocyclic compounds formation ( Ziegleder, 2009 ). Ketones are generally derived from amino acid and lipid degradation with the presence of these compounds having an impact on food flavor ( Adebo et al., 2018 ). Nine ketones were detected, i.e .…”
Section: Resultsmentioning
confidence: 99%